2016
DOI: 10.1007/978-3-319-33954-2_10
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic Routing of Unmanned Aerial Vehicles

Abstract: Various missions carried out by Unmanned Aerial Vehicles (UAVs) are concerned with permanent monitoring of a predefined set of ground targets under relative deadline constraints, i.e., the targets have to be revisited 'indefinitely' and there is an upper bound on the time between two consecutive successful scans of each target. A solution to the problem is a set of routes-one for each UAV-that jointly satisfy these constraints. Our goal is to find a solution with the least number of UAVs. We show that the deci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 4 publications
0
16
0
Order By: Relevance
“…A number of studies have assumed constant wind speed and wind direction [33] and used linear approximations for energy consumption [2]. The technical parameters of UAVs including the UAV dimensions, battery capacity and payload limits, and the aspects of changing weather conditions, including wind speed, wind direction, and air density, all influence the search for possible UAV mission planning solutions [3,12]. As the linear approximations reported in the current state are insufficient in terms of finding acceptable energy calculations for the UAVs considered in this research study [10], non-linear models proposed are used to calculate energy consumption in relation to weather conditions [4,15].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies have assumed constant wind speed and wind direction [33] and used linear approximations for energy consumption [2]. The technical parameters of UAVs including the UAV dimensions, battery capacity and payload limits, and the aspects of changing weather conditions, including wind speed, wind direction, and air density, all influence the search for possible UAV mission planning solutions [3,12]. As the linear approximations reported in the current state are insufficient in terms of finding acceptable energy calculations for the UAVs considered in this research study [10], non-linear models proposed are used to calculate energy consumption in relation to weather conditions [4,15].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Special attention is devoted to the UAVs flying mission planning following the delivery strategies assuming either that each UAV travels at a constant ground speed or constant airspeed throughout the mission.The solutions provide answers to whether a given level of customer satisfaction is achievable within a given time horizon. Similar problems have been considered in previous studies [12][13][14] and the focus of this study is on solutions that allow one to find a collision-free plan of delivery missions composed of a sequence of UAV multi-trip missions maximizing order fulfillment. This research further proposes a declarative framework that allows one to formulate a reference model for the analysis of the relationships between the structure of a given UAV-driven supply network and its resistance to weather as a result of the sequence of UAVs' routes and schedules.…”
mentioning
confidence: 99%
“…In [2], the behaviors of each sub-system, including the ground control station, the ground vehicle, a micro aerial vehicle, a high level UAV are investigated and captured and a Kripke model is used to formally describe the system. In [3] and [4], the Cyclic Routing problem of UAVs is formally defined and a lower-bound on the number of required UAVs is obtained. In [5], the authors have shown that the Cyclic Routing of UAVs problem is polynomial space PSPACE-complete.…”
Section: Introductionmentioning
confidence: 99%
“…In this work, we consider the Cyclic-Routing UAV Problem (cr-uav) [8]: the decision version of a simple recurrent UAV path-planning problem in which each target must be visited not only once but repeatedly, i.e., at intervals of prescribed maximal duration. Problems of this type have long been considered in many other fields such as transportation [16,22] and robotics [7,12].…”
Section: Introductionmentioning
confidence: 99%